PERTUMBUHAN DAN PRODUKSI BABY KAILAN (Brassica alboglabra L.) DENGAN PEMBERIAN TRICHO-KOMPOS TANDAN KOSONG KELAPA SAWIT - Faisal Fajri F; Armaini '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of the research was to determine growth and production of baby kailan (Brassica alboglabra L.) with giving Tricho-compost empty bunch of oil palm and get the best treatment for growt hand production of baby kailan. This research was conducted at the land of the Laboratory of Plants of Agriculture Faculty, University of Riau for 2 months. The research used Randomized Block Design (RBD) consisted of 5 treatments with four replications. The Tricho-compost empty bunch of oil palm treat ments as follows: P0 : Tricho-compost empty bunch of oil palm 0 ton/ha, P1 : Tricho-compost empty bunch of oil palm 3 ton/ha, P2 : Tricho-compost empty bunch of oil palm 6 ton/ha, P3 : Tricho-compost empty bunch of oil palm 9 ton/ha and P4 : Tricho-compost empty bunch of oil palm 12 ton/ha. Data were analyzed by analysis of variance and further test DNMRT at 5% level. Parameters observed were: plant height, number of leaves, leaf area, root volume, plant fresh weight per plot and weight of crop suitable for consumption per plot. The results showed application of Tricho-compost empty bunch of oil palm significantly affect to all parameters tested. The treatment of Tricho-compost empty bunch of oil palm 12 ton/ha is the best concentration for all parameters tested. Keyword : Brassica alboglabra L., tricho-compost empty bunch of oil palm